2021
DOI: 10.1002/vro2.8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of protective level of rabies antibodies in vaccinated dogs in Chennai, India

Abstract: Background Rabies is still endemic in India causing an estimated 20,000 human deaths a year. Free roaming dogs and unvaccinated owned dogs play a major role in the maintenance of the disease. Dog vaccination is the most crucial aspect of rabies prevention and control strategies; therefore vaccine immunogenicity and longevity are important determinants of the efficiency of rabies control efforts. Methods In this study at Madras Veterinary College, India, a total of 297 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…found that purebreds are more likely to seroconvert. 54 We found similar trends to other previous studies as well ( Figure 1D ), but these trends were not statistically significant. One potential explanation for the higher rabies antibody titers found in females and small/medium dogs is that they are easier to handle and therefore are vaccinated more frequently than larger or male dogs.…”
Section: Discussionsupporting
confidence: 91%
“…found that purebreds are more likely to seroconvert. 54 We found similar trends to other previous studies as well ( Figure 1D ), but these trends were not statistically significant. One potential explanation for the higher rabies antibody titers found in females and small/medium dogs is that they are easier to handle and therefore are vaccinated more frequently than larger or male dogs.…”
Section: Discussionsupporting
confidence: 91%
“…Another conclusion drawn from the results of this study is that unsterilized males are more likely to be unprotected. A recent study in India supports these conclusions, showing that neutered dogs are approximately four times more likely to present antibody titers than unsterilized dogs [71]. Thus, it is indisputable that an animal's reproductive status and hormones, mainly testosterone, influence the immune response [72].…”
Section: Discussionmentioning
confidence: 91%
“…An earlier study from Chandigarh, India, observed that only 1% of street dogs had adequate titres [ 22 ], as evaluated by using a commercially available ELISA. Another sero-surveillance study using an iELISA from Mumbai showed an overall low seroprevalence of anti-RABV antibody in stray dogs at the level of 39.2% [ 23 ] and a study from Chennai revealed an inadequate titre in 60% of vaccinated dogs [ 24 ]. Similar results of inadequate levels (i.e., 62%) have been reported in stray dogs in Bangkok, where a commercial ELISA was used [ 25 ].…”
Section: Discussionmentioning
confidence: 99%